Risk stratification in patients with unstable angina and diabetes mellitus - R. D. Kurbanov; R. Kh. Trigulova; A. B. Shek; N. F. Tashkenbaeva (Кардиоваскулярная терапия и профилактика)
Aim. To identify the adverse outcome predictors in patients with unstable angina (UA) and Type 2 diabetes mellitus (DM-2).Material and methods. The study included 73 patients with first-diagnosed and progressing angina; the follow-up period lasted for 2 years. The adverse outcomes registered included: fatal and non-fatal myocardial infarction (MI), stroke, sudden death, and emergency-related repeat hospitalisation.Results. In patients with UA and DM-2, adverse outcome predictors included: previous MI, carotid artery intima-media thickness >0,9 mm, fasting glycemia >13 mmol/l and 2-hour postprandial glycemia >14,8 mmol/l, glucose level change >54 %, increased levels of total and low-density lipoprotein cholesterol.Conclusion. Fasting and postprandial glycemia, glucose level change and other factors are important in risk stratification among patients with UA and DM-2.